OP0257 Differential DNA Methylation Related to Response to Adalimumab and Etanercept in Patients with Rheumatoid Arthritis. (10th June 2014) - Webster, A.; Plant, D.; Eyre, S.; Wilson, G.; Morgan, A.; Isaacs, J.; Worthington, J.; Barton, A.
Abstract : Background: Anti-TNF therapies have proved a huge advance for the treatment of rheumatoid arthritis (RA), however very good disease control or remission is achieved in just 30% of patients. This makes the identification of biomarkers predictive of response an important area of research. Such predictive biomarkers would allow the most effective treatment for a patient to be identified early in disease course. An increasing number of studies have identified a role for epigenetics in RA and other autoimmune disorders, thus we hypothesised that epigenetic changes, such as DNA methylation, may provide potential biomarkers of response to anti-TNFs. Objectives: To identify methylation signatures predictive of response to anti-TNF therapies in patients with RA. Methods: Patients were selected from the Biologics in Rheumatoid Arthritis Genetics and Genomics Study Syndicate (BRAGGSS) longitudinal cohort. Patients (n=119) were selected based on having an extreme response phenotype after 3 months of treatment with etanercept or adalimumab; 36 were good responders to etanercept and 30 to adalimumab defined as having an endpoint DAS28<2.6, and 35 were poor responders to etanercept and 18 to adalimumab defined as having an improvement of <0.6 or between 0.6-1.2 with an endpoint DAS28 of >5.1. DNA from each patient, sampled before initiation of therapy, was bisulfite converted and an epigenome-wide association study was conducted using the HumanMethylation450 BeadChip (Illumina). The results from each drug were analysed separately using the minfi package in R and probes with a detection-p value >0.01 were removed. Differentially methylated positions between responders and non-responders were identified using the F-test following quantile normalisation. Results: In the etanercept study, four CpG sites showed differential DNA methylation that passed a false discovery rate of 0.05, while in the adalimumab study, two CpG sites passed this threshold. The most differentially methylated position in etanercept patients mapped to the LRPAP1 gene (p=1.46×10 -8 ). This gene encodes a chaperone of low density lipoprotein receptor-related protein 1 (LRP1) which is known to influence TGF-β activity. Technical validation of methylation at this site by pyrosequencing showed very good correlation (Spearmans r=0.8). In the adalimumab patients, the most differentially methylated position maps to the MAD2L2 gene. Conclusions: This is one of the largest methylome-wide investigations of treatment response to anti-TNF therapies in RA. These preliminary results identify DNA methylation as a potential biomarker of response for etanercept and adalimumab. Acknowledgements: This work was supported by the innovative medicines initiative joint undertaking (IMI JU) funded project BeTheCure, (contract number 115142-2). Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4104